Juvenile Delinquency in the Perspective of Criminology in Indonesia: A Systematic Literature Review - Saragih, Krissi Wahyuni; Suhendar, Aris; Damanik, Juliardi; Girsang, Ravina Novriani; Saragi, Sinta Rahayu; Ningrum, Wahyu Canda (Program Pascasarjana UIN Sumatera Utara, 2025)
Juvenile delinquency remains a growing social challenge in Indonesian society, encompassing various forms of deviant behavior such as student brawls, drug abuse, illegal street racing, and acts of group violence frequently occurring within educational environments and urban communities. This phenomenon not only poses a threat to social stability but also signals the weakening of social control functions and the failure of character-building systems for adolescents. This study aims to identify the causal factors of juvenile delinquency, evaluate the countermeasures that have been implemented, and analyze the relationship between criminological theory particularly the Differential Association Theory and the practice of juvenile delinquency prevention in Indonesia. The method used is a systematic literature review (SLR) of various scientific publications from the past five years, sourced from open-access databases and reputable journals. The data were analyzed using a content analysis approach to synthesize thematic patterns from relevant empirical and theoretical findings. The results indicate that juvenile delinquency is primarily triggered by negative social environments, weak emotional bonds within families, and close association with deviant peer groups. Repressive approaches to addressing delinquency have proven ineffective, as they overlook the sociological roots of such behavior. This study concludes that preventive, community-based interventions that emphasize value education are key to addressing juvenile delinquency systemically. These findings provide an important contribution to the development of evidence-based policy strategies and the design of more contextually relevant social intervention programs in Indonesia.